PREFERENSI KONSUMEN IKAN LAUT SEGAR BENGKULU ATAS BRAND EQUITY SEBAGAI JAMINAN KUALITAS PRODUK - Bonodikun, Bonodikun; Asriani, Putri Suci; Budiyanto, Budiyanto (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
Fisheries products in Bengkulu Province are still not to be classified well, so it may be considered not necessary to develop the discourse of product quality assurance. Regardless, the demands of globalization require each manufacturer to think ahead about the quality of the product